2010
DOI: 10.1186/1758-3284-2-32
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes in head and neck cancer: selecting instruments for quality of life integration in clinical protocols

Abstract: BackgroundHealth Related Quality of Life has been used in medical research for more than twenty years, being progressively accepted during the last decade as an important patient reported outcome. Considering the multidimensional approach involved in Health Related Quality of Life assessment, instrument applicability and cultural adaptation must be tested for each population. In order to select the most appropriate instrument for Head and Neck cancer patients, two major Health Related Quality of Life specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
2
14
0
1
Order By: Relevance
“…The results show that, in relation to the demographic and clinical characteristics, the study population was predominantly male (8 men for each woman), less than 60 years old, white, of low educational level, and at the time of the interview lived with a companion, had clinical staging IV, and had undergone radiotherapy. Similar results have been obtained in other studies where the patients with laryngeal cancer were mostly men and with low educational level [3,4,14]. The replies to the questions concerning the subjective domains of the questionnaire showed that 78.9% of the patients considered their quality of life to be good to excellent and 90.5% indicated that their health was equal to or better than before diagnosis.…”
Section: Discussionsupporting
confidence: 86%
“…The results show that, in relation to the demographic and clinical characteristics, the study population was predominantly male (8 men for each woman), less than 60 years old, white, of low educational level, and at the time of the interview lived with a companion, had clinical staging IV, and had undergone radiotherapy. Similar results have been obtained in other studies where the patients with laryngeal cancer were mostly men and with low educational level [3,4,14]. The replies to the questions concerning the subjective domains of the questionnaire showed that 78.9% of the patients considered their quality of life to be good to excellent and 90.5% indicated that their health was equal to or better than before diagnosis.…”
Section: Discussionsupporting
confidence: 86%
“…The UW-QOL has an overall internal consistency with a Cronbach alpha of 0.85. The test-retest reliability coefficient was 0.95 (Silveira et al, 2010;Weymuller, Alsarraf, Yueh, Deleyiannis, & Coltrera, 2001).…”
Section: Introductionmentioning
confidence: 94%
“…The objective of this study was not to evaluate patients' survival, but many deaths were found among patients with oral cavity cancer. Rogers et al 16 stated that even with the combination of extensive surgery and adjuvant radiotherapy, studies show that curative treatment occurs only in the minority of cases and that less than 30% of patients will survive after 5 years 27 .…”
Section: Tumors / Lip and Oral Cavity Tumorsmentioning
confidence: 99%